Incentive Value and Brain Electrophysiology in a Target/Nontarget Discrimination Task - Jablonski, Paige M.; Kroner, Kellyn A.; Bradley, Jacob; Barber, Danielle; Soderholm, Beatrice R.; Johnson, Amy R.; Vanlandschoot, Emily; Hanley, Eric (My University, 2012)
Event-Related Potential (ERPs) are electrical responses from the brain recorded from the EEG when a person perceives something and responds to it. The N1 component reflects early sensory processing, especially sensitive to stimulus discrimination tasks. The P3 component reflects later stimulus evaluation and categorization, maximized by stimuli that are infrequent, task-relevant, and/or motivationally salient. The purpose of this study was to look at how motivation influences the neural basis of attention, specifically the N1 and P3 components and looked at whether manipulating points earned for correct responses to stimuli influences N1 and/or P3.
Color poster with text, images, and graphs.
Keywords: Brain; Electrophysiology; Reward (Psychology); Psychological tests; Posters